Indonesian Market Volatility During the COVID-19 Pandemic: Foreign versus Domestic Investors - Suhernita, Suhernita (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2024)
This study examines the effect of institutional ownership on stock price volatility before and after the announcement of the first confirmed COVID-19 cases in Indonesia. The sample includes all public companies listed on the Indonesian stock exchange minus financial firms. Data for this study were retrieved from the Osiris database. The results of this study indicate that when a market was relatively stable (before the discovery of the COVID-19 pandemic in Indonesia), there was no effect of institutional ownership on stock price volatility. However, after the announcement of confirmed COVID-19 cases, this study finds a positive influence of institutional ownership on stock price volatility. This research contributes in two important ways. First, the previous study predicts that extreme market volatility is a signal of an incoming recession. This situation should alarm various stakeholders to anticipate potential unexpected outcomes. Second, institutional investors play a crucial role in the market. Understanding their trading behavior during the pandemic period provides insight for various stakeholders in the decision-making process.